NAFTA or not: implications for CARICOM agricultural competitiveness - Antoine, Patrick A. (IICA BridgetownBB, 1993)
Presents an overview of NAFTA and looks at the implications for CARICOM agriculture. Examines four categories of economic factors viz. investment, productivity, demand and cost. Analyses four specific commodities - citrus; sugar; fish and fish products; and rum, and makes conclusions.